A Sustainable Multipurpose Separator Directed Against the Shuttle Effect of Polysulfides for High‐Performance Lithium–Sulfur Batteries. Issue 19 (8th April 2022) - Wang, Wei; Xi, Kai; Li, Bowen; Li, Haojie; Liu, Sheng; Wang, Jianan; Zhao, Hongyang; Li, Huanglong; Abdelkader, Amor M.; Gao, Xueping; Li, Guoran
Abstract: The success of lithium–sulfur batteries will reduce the expected Co, Ni resource challenges from the wide adoption of lithium‐ion batteries. Unfortunately, the shuttle effect of soluble polysulfides brings many problems. Anchoring or blocking polysulfides on the cathode side using functional separators is the dominant strategy for addressing this. However, the blocked polysulfides gradually aggregate on the separator to form the so‐called "dead sulfur" and withdraw from cycling. Herein, a multipurpose separator is proposed that enables catalytic activation of the blocked polysulfides to prevent the formation of "dead sulfur", and contribute to capacity. The multifunctionality is supported by montmorillonite (MMT) that provides sufficient channels for lithium‐ion transport, and selenium‐doped sulfurized‐polyacrylonitrile (Se0.06 SPAN) that catalyzes conversion of "dead sulfur" and simultaneously contributes capacity. The theoretical calculations reveal Se0.06 SPAN/MMT has a low migration barrier for Li + and a low decomposition barrier for Li2 S, facilitating the conversion and minimizing "dead sulfur". Consequently, the Li–S battery with the Se0.06 SPAN/MMT@PP (polypropylene) separator shows a low fading rate of 0.034% during 1000 cycles and achieves a super‐high areal capacity (33.07 mAh cm –2 ) under high sulfur loading (26.75 mg cm –2 ) and lean electrolyte conditions (4.5 µL mg –1 ). Moreover, the multipurpose separator has encouraging performance in stability, flexibility, and sustainability. Abstract : A multipurpose separator, selenium‐doped sulfurized‐polyacrylonitrile/montmorillonite (Se0.06 SPAN/MMT)@polypropylene, effectively restrains the polysulfide shuttle, catalyzes the conversion of polysulfides, and contributes to capacity, to help lithium–sulfur batteries achieve excellent performance. Moreover, the separator can be reused for stability, flexibility, and sustainable performance.